Heat Kernel Measure on Central Extension of Current Groups in any Dimension - Léandre, R. (Symmetry, Integrability and Geometry: Methods and Applications, 2006)
We define measures on central extension of current groups in any dimension by using infinite dimensional Brownian motion.